Manajemen Peserta Didik dalam Meningkatkan Prestasi Santri di Pondok Pesantren Ora Aji Sleman: Learner Management in Improving Santri Achievement at Pondok Pesantren Ora Aji Sleman - Sugiarto, Danu; Maghfiroh, Ana Miniswatil (CV. Kalimasada Group, 2023)
Student management is an important aspect in educational institutions because it aims to regulate student activities to support the learning process. In the world of Islamic boarding schools, student management needs to be carried out so that students do not only have good morals, but also have proud achievements. This study aims to determine the student management process carried out at the Ora Aji Islamic boarding school in order to improve student achievement. The research method used in this study is a qualitative method with a case study approach. Research data obtained through observation, interviews, and documentation then analyzed with descriptive techniques. The results of the study showed that the management of students carried out at the Ora Aji Islamic boarding school included: acceptance of students, class division, coaching, evaluation and monitoring. With the management of students, students are proven to be able to achieve by winning several competitions that are participated outside the boarding school.